PECULIARITIES OF IMPROVING THE MANAGEMENT SYSTEM IN INTERNAL AFFAIRS BODIES (Scientific journal of the Fergana State University, 2023)
Comprehensive work aimed at improving the system of internal affairs bodies in new Uzbekistan, strengthening their lower links closer to the population, clearly defining the tasks and functions of structures at all levels, rational distribution of forces and means taking into account modern risks is being implemented. In the article, the specific features of the management system of internal affairs bodies, legal bases, information provision of the management system, material and technical support of the management system, priority areas of management improvement, introduction of innovative projects into the system, as well as issues such as the management system suggestions for improvement have been put forward.